1973
DOI: 10.1111/j.1471-4159.1973.tb07561.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SYNTHESIS OF CHOLINE AND ETHANOLAMINE PHOSPHOGLYCERIDES IN NEURONAL AND GLIAL CELLS OF RABBIT IN VITRO1

Abstract: Abstract— The de novo synthesis of phosphatidylcholine and phosphatidylethanolamine in isolated neuronal and glial cells from adult rabbit brain cortex was investigated in vitro, using labelled phosphorylcholine (phosphorylethanolamine) or cytidine‐5′‐phosphate choline (cytidine‐5′‐phosphate ethanolamine), as lipid precursors. Synthesis of phospholipid from phosphorylcholine and phosphorylethanolamine in both fractions was extremely low when compared to that derived from the corresponding cytidine nucleotides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
29
0
1

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 36 publications
12
29
0
1
Order By: Relevance
“…1). Somewhat similar findings were observed for diacyl-GPE synthesis (1). During the incubation period of 30 rain, formation of products (diacyl-GPE or alkenylacyl-GPE) from CDPE was proportional to the amount of neuronal or glial protein over the range from 0.5-2.0 mg/ml.…”
Section: Properties Of Ethanolamine-phosphotransferasesupporting
confidence: 82%
See 1 more Smart Citation
“…1). Somewhat similar findings were observed for diacyl-GPE synthesis (1). During the incubation period of 30 rain, formation of products (diacyl-GPE or alkenylacyl-GPE) from CDPE was proportional to the amount of neuronal or glial protein over the range from 0.5-2.0 mg/ml.…”
Section: Properties Of Ethanolamine-phosphotransferasesupporting
confidence: 82%
“…Neuronal and glial cells have been studied recently in vitro in a variety of biochemical reactions (1), including protein synthesis (2). No reports have as yet appeared, however, on the ability of these cells to perform phospholipid biosynthesis, except for some studies on the base-exchange reaction (3)(4)(5) and on the synthesis of 1,2-diacyl-sn-glycero-3-phosphorylcholine 1presented in part at the IXth International Congress of Biochemistry, Stokholm, July 1973 and at the XIXth National Meeting of Biochemistry, Trieste, October 1973.…”
Section: Introductionmentioning
confidence: 99%
“…The identified spots were scraped off the plate and eluted several times with chloroform-methanol-acetic acid-water (50: 39: 1 : 10, by vol). Eluates were dried under a stream of nitrogen in counting vials and counted according to BINAGLIA et al (1973) in a Model 3375 Packard liquid scintillation spectrometer, using the external standard method for quench correction. With control experiments it was observed that nearly all the original radioactivity of pure reference standards could be recovered by using this procedure.…”
Section: Methodsmentioning
confidence: 99%
“…We have found evidence for the presence of CDP-ethanolamine: 1,2diacyl-sn-glycerol ethanolaminephosphotransferase (EC 2.7.8.1), which catalyzes the last step in the biosynthesis of phosphatidylethanolamine and related ethanolamine glycerophospholipids (Kennedy and Weiss, 1956). Its presence in nervous tissue has been well documented (Porcellati et al, 1970;Ansell and Metcalfe, 1971; Radominska-Pyrek and Horrocks, 1972;Binaglia et al, 1973;Roberti et al, 1975;Freysz et al, 1977;Radominska-Pyrek et al, 1977;Dreyfus et al, 1978).…”
mentioning
confidence: 98%